Deploying Microsoft Forefront Protection 2010 for Exchange Server - Diogenes, Yuri (Microsoft Press, 2010)
"This book is targeted at information technology professionals, security consultants and firewall administrators who wish to design, develop and implement the Microsoft Forefront security products on their Microsoft and heterogeneous networks."--Resource description page.